Systematic Approach to a Case of Disc Pallor - Digvijay Singh; Rohit Saxena; Pradeep Sharma; Vimla Menon (Delhi Journal of Ophthalmology)
Disc pallor is often the sequel of various optic nerve disorders and signifies partial or total optic atrophy. It may be present with symptoms or signs ranging from subtle visual dysfunction to total blindness or may even be an incidental finding during routine ophthalmological checkup. Discovering the cause of such a case can baffle neurologists and ophthalmologists alike. We describe a systematic clinically oriented approach to a case of disc pallor to help arrive at a diagnosis.